Emotion recognition and cognitive empathy deficits in adolescent offenders revealed by context-sensitive tasks - Gonzalez-Gadea, Maria Luz; Herrera, Eduar; Parra, Mario; Gomez Mendez, Pedro; Baez, Sandra; Manes, Facundo; Ibanez, Agustin (Frontiers in Human Neuroscience, 2014)
Emotion recognition and empathy abilities require the integration of contextual information in real-life scenarios. Previous reports have explored these domains in adolescent offenders (AOs) but have not used tasks that replicate everyday situations. In this study we included ecological measures with different levels of contextual dependence to evaluate emotion recognition and empathy in AOs relative to non-offenders, controlling for the effect of demographic variables. We also explored the influence of fluid intelligence (FI) and executive functions (EFs) in the prediction of relevant deficits in these domains. Our results showed that AOs exhibit deficits in context-sensitive measures of emotion recognition and cognitive empathy. Difficulties in these tasks were neither explained by demographic variables nor predicted by FI or EFs. However, performance on measures that included simpler stimuli or could be solved by explicit knowledge was either only partially affected by demographic variables or preserved in AOs. These findings indicate that AOs show contextual social-cognition impairments which are relatively independent of basic cognitive functioning and demographic variables.